Good Recruitment Process Contributes to Happy and Satisfied Employees – A Study with Reference to A Public Enterprise in Visakhapatnam, Andhra Pradesh, India - Suneetha RAPAKA (Communications of International Proceedings, 2023)
Do not hire a man who does your work for money, but him who does it for the love of it. “ – This is the central theme of the research paper. The research was carried out to test whether there is a significant relationship between the efficiency of the Recruitment and Selection Process ,  Job Satisfaction and Planned Period of Employee Stay. A public enterprise in the city of Visakhapatnam, Andhra Pradesh, India was selected and a sample of 100 Respondents was considered. The Recruitment and Selection Procedure at the public enterprise was studied. The research findings showed that there is a significant relationship between the efficiency of the Recruitment and Selection Process and Job Satisfaction. And also, there is a significant relationship between the efficiency of the Recruitment Process and the Planned period of employee Stay in the organization. The researcher came up with suggestions like using Technology for better recruitment, using HR Analytics, highlighting the importance of the job and the difference an employee can make on his job, and the inner drive and personality of the candidates can be used while selecting them for the job. Employees who are satisfied with the job would stay in the company for a long period and so the efficiency of the recruitment process reflects on this. Ultimately, be it a human recruiter or Artificial Intelligence tool, it is all about recruiting people, who love doing their job and finding meaning in their work.
Keywords: Recruitment; Selection; Job Satisfaction; Employee Retention